Pelatihan Pengembangan Produk Kain Ulos sebagai Suvenir Khas Desa Meat Toba Samosir - Christmastuti Nur (Servirisma, 2022)
The Ministry of Tourism has named Lake Toba in North Sumatra as one of the five super priority destinations in Indonesia. Meat Village, which is located on the edge of Lake Toba, has also become one of tourism points development because it is not only rich in natural beauty but also has strong artistic and cultural elements. This training aims to empower the community, especially housewives, in developing the potential of ulos woven fabrics as souvenirs from the tourist village of Meat. This Community Service program was initiated by collecting data through interviews, surveys, and observations with the community and local village officials regarding the types, processes of making and marketing ulos cloth. The next stage is to organize a Training for Trainers (ToT) in order to assist participants in the training. The training was held for 2 days and was attended by 37 participants. On the first day of the training, participants were trained to make special packaging and shopping bags for the Ragi Hotang ulos cloth, the weaving process of which is one of the tourist attractions of Meat Village. Packaging and shopping bags are an effort to form a positive Meat Tourism Village brand image. Then on the second day, participants practiced developing various products from Sadum ulos cloth. After participating in this training, it is hoped that the local community can market Meat Village souvenir products directly to tourists without going through intermediaries so as to further improve welfare. Through this souvenir product, it is also expected to help support the readiness of Meat Village as a tourist village.